Texture Evaluation for a Commercial Chili-Based Paste - Sobhi, Babak; Mohd Adzahan, Noranizan; Ab Karim, M. Shahrim; Karim, Roselina; Bakar, Jamilah; Abdul Rahman, Russly (2010)
Chili shrimp paste (CSP) is a traditional Southeast Asian condiment conventionally prepared using a granite mortar and pestle. It is a semi-solid suspension which contains chunky chili pieces. Textural characteristics of the pastes are important quality parameters for consumers as they prefer pastes with a certain degree of thickness and chunkiness. Unfortunately, there is no standard methodology available to evaluate textural properties of such pastes. The objectives of this study were to establish a method for size reduction of chilies suitable for commercial production of CSP and to determine the typical textural properties of CSP preferred by consumers. Various samples of CSP were prepared and evaluated through sensory and instrumental evaluations (back extrusion method and vane in cup). Chili shrimp pastes prepared using the super mass colloider can substitute traditional pastes prepared by manual pounding in mortar. The milled CSP can produce a uniform paste, similar to the traditionally mortar pounded CSP samples but with the advantage of a higher production capacity. Both instrumental (textural measurement) methods were found to be reliable and consistent methods which can be applied in quality control for textural properties of CSP in a commercial-scale production set-up.